On surfaces of general type with pg=6 and K2=13 - Neves, Jorge (2004)
We prove that the canonical model of a nonsingular surface of general type with pg = 6 and K2 = 13 whose canonical image is not contained in a pencil of quadrics is a complete intersection of four quasihomogeneous forms of degree 2 and two quasihomogeneous forms of degree 1 in the cone over a weighted Grassmannian